Counterfeit Currency Recognition Using Deep Learning: A Review - Muhamad, Sabat; Ahmed, Twana (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
This review article reviews some previous work in the literature about using deep learning techniques for recognizing fake notes from the real notes. A human-visual system can be utilized for identifying and confirming currency-notes. Yet, our eyesight cannot sense everything, and it is frequently hard for humans to recognize genuine currency without using technology assistance. Deep learning methods have been revealed to be more efficient for numerous applications. Consequently, deep learning has been used to enhance currency recognition accuracy. The methods that are used including Classic neural networks, CNN, and GANs for recognizing fake notes.